Internet of things based attendance system design and development in a smart classroom - Dania Eridani; Eko Didik Widianto; Ike Pertiwi Windasari; Wildan Budi Bawono; Nadia Febrianita Gunarto (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Attendance records are one of the main administrative roles on campuses. Therefore, several technologies can be used on an attendance system, including barcode, radio frequency identification (RFID), fingerprint, and faceprint. The main functions of attendance systems on campuses are mainly focused on how to obtain the attendee data list, store on the database, and display the list on the information system. This research proposes an attendance system in the smart classroom which supports the system’s previous activities as well as its integration with security and classroom management. In this system, the NodeMCU which was connected to the Wi-Fi router served as the controller, while the fingerspot revo FF-153BNC functioned as the system input. In addition, the database server was used to allocate attendee and classroom management data. This system is connected with the information system and classroom display unit, and component and system testing were applied in this research. The results showed that each system unit successfully integrated and managed the attendance, security, and classroom schedule.